Coulomb Interactions and the Spatial Coherence of Femtosecond Nanometric Electron Pulses - Meier, Stefan; Hommelhoff, Peter (ACS Photonics, 2022)
The transverse coherence of electrons is of utmost importance in high resolution electron microscopes, point-projection microscopes, low-energy electron microscopy, and various other applications. Pulsed versions of many of these have recently been realized, mostly relying on femtosecond laser-triggering electron emission from a sharp needle source. We here observe electron interference fringes and measure how the interference visibility becomes reduced as we increase the emitted electron bunch charge. Due to the extremely strong spatiotemporal confinement of the electrons generated here, we observe the visibility reduction already at average electron bunch charges of less than 1 electron per pulse, owing to the stochastic nature of the emission process. We can fully and quantitatively explain the loss of coherence based on model simulations. Via the van Cittert-Zernike theorem, we connect the visibility reduction to an increase in the effective source size. We conclude by discussing emittance, brightness, and quantum degeneracy, which have direct ramifications to many setups and devices relying on pulsed coherent electrons.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Coherence; Electron correlations; Electron interference; Electron optics; Femtosecond lasers; Ultrafast electron emission